The Determinants of Accounting Prudence Among Infrastructure Sector Companies in Indonesia - Revita Handayani, Angela Sherly; Yanto, Heri (AFEBI Accounting Review, 2024)
This study aims to identify the factors influencing the application of accounting prudence in Indonesian infrastructure sector companies. These factors encompass capital intensity, growth opportunities, company size, profitability, leverage, and audit committees. A quantitative approach is employed in this research, with the population consisting of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sample selection utilizes purposive sampling techniques, resulting in a final sample of 35 companies with a 5-year observation period, comprising 114 analyzable units of data. Descriptive and inferential statistical analyses are conducted using IBM SPSS version 26. The research findings indicate that capital intensity, company size, profitability, and leverage significantly impact accounting prudence. However, growth opportunities and audit committees do not have a significant effect on accounting prudence. The novelty of this study is in the simultaneous utilization of 6 independent variables. Previous study has not used these 6 independent variables simultaneously. The population consists of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022.